Strategi Marketing Public Relations Melalui Pelayanan Digital Kabayan Pasti - Khoerunnisa, Lulu; Maarif, Abdul Aziz (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to describe the public relations marketing strategy of the Ministry of Law and Human Rights of West Java through the Kabayan Pasti digital service. The research method used is descriptive qualitative method. The results show that the marketing public relations strategy implemented by the Public Relations of the Ministry of Law and Human Rights of West Java is through three strategies, namely 1) pull strategy (attract public attention) through providing information about Kabayan Pasti and the use of social media, 2) push strategy (strategy to encourage public interest) by providing research facilities in using Kabayan Pasti and being responsive to the community, 3) through strategies (influence strategies to form opinions) through stakeholder relationships and community satisfaction surveys.